Performance of cryptococcal antigen lateral flow assay in serum, cerebrospinal fluid, whole blood, and urine in HIV-infected patients with culture-proven cryptococcal meningitis admitted at a Brazilian referral center - Vidal, José E.; Toniolo, Carolina; Paulino, Adriana; Colombo, Arnaldo L.; Martins, Marilena dos Anjos; Meira, Cristina da Silva; Azevedo, Renata Guise Soares; Pereira-Chioccola, Vera Lucia; Gomes, Hélio Rodrigues; Lazera, Marcia dos Santos; Oliveira, Augusto C. Penalva de; Boulware, David R. (Revista do Instituto de Medicina Tropical de São Paulo, 2018)
Cryptococcal meningitis is the most common cause of opportunistic meningitis in HIV-infected patients in Brazil and causes unacceptable high mortality rates. In this study, HIV-infected patients with a first episode of culture-proven cryptococcal meningitis in cerebrospinal fluid (CSF) were prospectively included in order to evaluate sensitivity of cryptococcal antigen (CrAg) lateral flow assay (LFA) in serum, CSF, whole blood (fingerstick), and fresh urine. In addition, HIV-infected patients with other neurological confirmed diseases were included in order to evaluate the specificity of CrAg LFA in serum. Twenty patients with cryptococcal meningitis were included and in 19 of them, CrAg LFA in CSF, serum, and whole blood were positive (95% sensitivity). In 18 patients, India ink test was positive in CSF (90% sensitivity), and in 16 cases, CrAg LFA was positive in urine (80% sensitivity). Thirty-six HIV-infected patients with other neurological diseases had negative results of CrAg LFA in serum (100% specificity). In conclusion, CrAg LFA in serum, CSF, and whole blood showed high sensitivity and specificity. Whole blood CrAg LFA seems to be a good and reliable strategy to improve AIDS-related cryptococcal meningitis diagnosis in Brazil.